Application Of Passage Plan To Avoid Ship Aground In Barito River: Case Study On Km. Fleet Fresh - Kumoro Jati, Septria; Iskandar; Nurhidayati, Indah (Nama Jurnal Akmi, 2025)
In the world of shipping, passage plans play an important role in improving the efficiency and safety of ship operations when sailing, so that narrow shipping channels are very useful because there are many dangerous areas of navigation in these areas. Ship incidents are often caused by external factors such as weather and track conditions, as well as human error in the operation of the ship. The passage plan is the most common strategy that aims to direct ships from one location to another safely, quickly, and efficiently. This study, entitled "Application of Passage Plan to Avoid Stranded Ships on the Barito River: A Case Study on KM. Armada Segara," uses a qualitative descriptive method with data collected through observation, interviews, documentation, and literature studies. The results of the study show that the implementation of a passage plan can reduce the risk of hazards during the voyage, although challenges such as equipment damage and weather uncertainty remain. So that it can be concluded in this study, before the start of the voyage, it is good to plan a good voyage and implement the passage plan according to the steps that have been set so that a safe voyage to the destination is created.